The service model of a MBA with humanistic approach - Barrera Duque, Ernesto (Cuadernos de Administración, 2011)
This research had the objective to establish the key elements of a student´s experience in a Colombian MBA program. Through narrative analysis and grounded theory, both qualitatitive methods, key categories were found for service experience. Professor’s interaction, couch’s interaction, organization’s context, interaction with other students, and participant centric program design, were key drivers in this experience. Besides, case method was found as an important mediator in delivering a practical experience. Finally, the consequences of the experience were: skill development and integral personal transformation. The humanistic focus embedded in each category was a connector among them, and confirming its importance for an oriented performance education. The participants appreciate this humanistic approach.